2021
DOI: 10.1590/0037-8682-0599-2020
|View full text |Cite
|
Sign up to set email alerts
|

Role of aminoglycoside-modifying enzymes and 16S rRNA methylase (ArmA) in resistance of Acinetobacter baumannii clinical isolates against aminoglycosides

Abstract: INTRODUCTION: This study aimed to determine the role of genes encoding aminoglycoside-modifying enzymes (AMEs) and 16S rRNA methylase (ArmA) in Acinetobacter baumannii clinical isolates. METHODS: We collected 100 clinical isolates of A. baumannii and identified and confirmed them using microbiological tests and assessment of the OXA-51 gene. Antibiotic susceptibility testing was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…In contrast to the findings of the current study and the findings of Nie et al 31 a relatively low prevalence rate of 33% for ant(3ʹ)-Ia was reported by the recent Iranian study conducted by Jouybari et al 57 among A. baumannii clinical isolates.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings of the current study and the findings of Nie et al 31 a relatively low prevalence rate of 33% for ant(3ʹ)-Ia was reported by the recent Iranian study conducted by Jouybari et al 57 among A. baumannii clinical isolates.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, 19 different genetic aminoglycoside resistance profiles were detected. In the same context, 22 aminoglycoside resistance genetic profiles were reported by the Iranian study that was conducted by Jouybari et al 57 indicating that the Iranian A. baumannii clinical isolates are more genetically diverse than Saudi isolates.…”
Section: Discussionmentioning
confidence: 70%
“…The minimum inhibitory concentrations (MICs) were determined using the agar dilution method following the guidelines of the Clinical and Laboratory Standards Institute (CLSI), and the susceptibility patterns were interpreted according to the CLSI breakpoint criteria ( CLSI, 2019 ). The antibiotics tested in this work included 10 aminoglycoside antibiotics (kanamycin, neomycin, ribostamycin, tobramycin, sisomicin, netilmicin, spectinomycin, amikacin, micronomicin, and streptomycin), six β-lactam antibiotics [aztreonam, ceftazidime, cefepime, cefoxitin, meropenem, and ampicillin (AMP)], two quinolone antibiotics (nalidixic acid and ciprofloxacin), two chloramphenicol antibiotics (chloramphenicol and florfenicol), fosfomycin, tetracycline, and polymyxin B. Additionally, as no CLSI breakpoints existed for streptomycin and spectinomycin, so the MIC results for the two antibiotics were interpreted according to the publications by Hu et al (2017) and Jouybari et al (2021) , respectively. Escherichia coli ATCC 25922 was used as a reference strain for quality control.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, A. baumannii exhibits resistance rates ranging from 80.0 to 90.0% against tobramycin, amikacin, and gentamicin [ 23 ]. Broad-spectrum aminoglycoside (amikacin, gentamicin, kanamycin, and tobramycin) resistance has then been attributed to ribosomal modifications (16S rRNA methylases: rmtA to rmtD ) and non-enzymatic mechanisms such as the overexpression of RND (AdeABC) or multiple antibiotic and toxin extrusion (MATE: AbeM) superfamily efflux pumps [ 24 , 25 ] ( Table 1 ). Similarly, efflux systems including the MATE superfamily efflux pump (AbeM), RND superfamily type efflux systems (AdeABC, AdeFGH, and AdeIJK), and Small Multidrug Resistance (SMR) protein family (AbeS) have been associated with quinolone resistance amongst A. baumannii strains [ 26 ].…”
Section: Acinetobacter Baumannii Resistome—antibiotic Resist...mentioning
confidence: 99%